1992
DOI: 10.1016/0035-9203(92)90086-r
|View full text |Cite
|
Sign up to set email alerts
|

Kala-azar: a comparative study of parasitological methods and the direct agglutination test in diagnosis

Abstract: In a comparative study 88 patients were diagnosed as suffering from kala-azar (visceral leishmaniasis) using 3 parasitological methods simultaneously. Splenomegaly was absent in 4 cases. In 84 patients with splenomegaly, splenic aspiration appeared to be the most sensitive method (96.4%), followed by bone marrow aspiration (70.2%) and lymph node aspiration (58.3%). There was no relation between titres in the direct agglutination test and parasite load as determined by the number of parasitological methods whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
135
2
8

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 7 publications
2
135
2
8
Order By: Relevance
“…One of them was diagnosed with a liver abscess and the other a pulmonary abscess. DAT, despite being one of the cheapest, simplest and most sensitive for diagnosing VL 14 , does not differentiate between past and recent infections 35 . The DAT test was not a diagnost criterion for co-infection study.…”
Section: Discussionmentioning
confidence: 99%
“…One of them was diagnosed with a liver abscess and the other a pulmonary abscess. DAT, despite being one of the cheapest, simplest and most sensitive for diagnosing VL 14 , does not differentiate between past and recent infections 35 . The DAT test was not a diagnost criterion for co-infection study.…”
Section: Discussionmentioning
confidence: 99%
“…22 Zijlstra and others found a sensitivity of 93.1%, 67.8%, and 56.3% for splenic, bone marrow, and lymph node aspiration, respectively, in a study of 91 hospital patients. 23 In an extensive community survey in Bangladesh, only 29 (23%) of 125 clinically suspected persons were parasitologically proven, and all responded favorably to treatment. 24 Although response to treatment is probably the best methodologic option in establishing a gold standard for VL, few related studies have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…These tests still remain the gold standard (GS) because of high specificity. 7,8 The aspiration materials result in a suboptimal sensitivity ranging from 93.1-98.7% for spleen aspirates to 52-85% for bone marrow and 52-58% for lymph node aspirates. However, these methods are invasive, risky, and painful; they require skilled personnel, and they are not readily available in disease-endemic regions.…”
Section: Introductionmentioning
confidence: 99%